THE IMPORTANCE OF THE ENGLISH LANGUAGE IN THE FORMATION OF MEDICAL TERMINOLOGY (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article delves into the significance of the English language in shaping and establishing medical terminology. Through a comprehensive exploration of literature, linguistic analysis, and the examination of historical developments, the article seeks to elucidate the pivotal role English plays in fostering effective communication within the global medical community.